2000
DOI: 10.1063/1.1289515
|View full text |Cite
|
Sign up to set email alerts
|

Ge composition in Si1−xGex films grown from SiH2Cl2/GeH4 precursors

Abstract: Effect of steady-state hydrogen coverage on the evolution of crosshatch morphology during Si 1−x Ge x / Si (001) growth from hydride precursors Chemical vapor deposition of undoped and in-situ boron-and arsenic-doped epitaxial and polycrystalline silicon films grown using silane at reduced pressure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…We had indeed observed in this temperature range a strong downwards bowing of such curves [14][15][16][17]. Good fits of our experimental data in the 650-750 1C range were indeed achieved using a x 2 =ð1 À xÞ ¼ nðFðGeH 4 Þ=F ðSiH 2 Cl 2 ÞÞ relationship [18] to link the Ge concentration x in our films to the F(GeH 4 )/ F(SiH 2 Cl 2 ) mass flow ratio. As an example, n ¼ 0:58 at 750 1C (same F(SiH 2 Cl 2 )/F(H 2 )=0.0025, no HCl) [15].…”
Section: Growth Parameters; Ge Concentration and Sige Growth Rate Detmentioning
confidence: 52%
“…We had indeed observed in this temperature range a strong downwards bowing of such curves [14][15][16][17]. Good fits of our experimental data in the 650-750 1C range were indeed achieved using a x 2 =ð1 À xÞ ¼ nðFðGeH 4 Þ=F ðSiH 2 Cl 2 ÞÞ relationship [18] to link the Ge concentration x in our films to the F(GeH 4 )/ F(SiH 2 Cl 2 ) mass flow ratio. As an example, n ¼ 0:58 at 750 1C (same F(SiH 2 Cl 2 )/F(H 2 )=0.0025, no HCl) [15].…”
Section: Growth Parameters; Ge Concentration and Sige Growth Rate Detmentioning
confidence: 52%
“…When using SiH 2 Cl 2 +GeH 4 gas mixtures at 550 1C, we see that the curve linking the Ge alloy composition x to the germane mixing ratio bow downwards from linearity for a constant SiH 2 Cl 2 flow. Suh and Lee [15] have demonstrated that, for a SiH 2 Cl 2 +GeH 4 chemistry, the gas flow ratio F(GeH 4 )/F(SiH 2 Cl 2 ) is linked to the Ge concentration through the following relationship: x 2 =ð1 À xÞ ¼ nðFðGeH 4 Þ=FðSiH 2 Cl 2 ÞÞ: We obtain a good fit of our SiH 2 Cl 2 +GeH 4 experimental data at 550 1C through this relationship, with a constant n equal to 2.66 for a F(SiH 2 Cl 2 )/ F(H 2 ) mass flow ratio of 0.0025. Were we to combine this n ¼ 2.66 value at 550 1C with those obtained at higher temperatures with exactly the same gaseous precursor flows and growth pressures (n ¼ 1.08 at 650 1C [16], n ¼ 0.66 at 700 1C [17] and n ¼ 0.55 at 750 1C [18]), the following relationship linking n to the absolute growth temperature T could be obtained: n (F( [17].…”
Section: The Sige Growth Kinetics On Bulk Blanket Wafersmentioning
confidence: 99%
“…As the energy barrier for H 2 desorption from the Ge surface is lower than that for H 2 desorption from the Si surface, the growth rate enhancement with increasing GeH 4 flow can be explained by the lowering of energy barriers for hydrogen desorption [ [17][18][19][20]. According to the literature [13,21] Compared with the reported result [21], our revised relationship implies that a higher Ge content could be obtained if SiGe films were deposited with the same parameters. Considering the effect of temperature on SiGe epitaxy, a reasonable explanation for this difference is that our actual epitaxial temperature is lower than the nominal temperature, because the thermocouple is not in contact with the Si substrate when SiGe is deposited.…”
Section: Dependence Of Sige Growth Rate and Ge Content On Geh 4 Flowmentioning
confidence: 43%